Influence of the Type Of Anesthesia On The Rate Of Maturation Of Arteriovenous Fistulas In Patients On Hemodialysis Protocol - Aurora, Loza Correa; María, Romero Santana Gisela; Arnulfo, Calixto Flores (South Eastern European Journal of Public Health, 2024)
This article aims to determine if the type of anesthesia influences the maturation rate of arteriovenous fistulas (AVF) in patients on hemodialysis protocol. To this end, an observational, retrospective study was carried out from the clinical records of patients who underwent AVF in the period December 2021-June 2022 at the ISSSTE Tláhuac Hospital. Information of interest was obtained from the records, including age, sex, anthropometric characteristics, comorbidities, anesthetic risk, type of anesthesia (BPB: brachial plexus block versus general anesthesia), fistula maturation, and complications. Descriptive and inferential statistical analysis was performed. A cutoff value of p ≤0.05 was considered significant. 45 patients with a mean age of 54.8±10.6 years were included. At three weeks post-fistula formation, the AVF maturation rate was 84.4%. At 6 months of follow-up, 97.8% of the fistulas were functional. Steal syndrome was the only complication and was found in 6.7% of patients. The Odds Ratio (OR) for fistula maturation in patients who underwent BPB was 8.1, 95%CI 1.3-48.8 (p=0.023). It can be concluded that the BPB is associated with a higher rate of AVF maturation for hemodialysis.